2002
DOI: 10.1067/mcp.2002.127112
|View full text |Cite
|
Sign up to set email alerts
|

Ribavirin dosing in chronic hepatitis C: Application of population pharmacokinetic‐pharmacodynamic models

Abstract: This simulation suggests that ribavirin dosage (in combination with pegylated interferon alfa-2b) for patients with chronic hepatitis C should be based on body weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
34
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 3 publications
2
34
0
Order By: Relevance
“…Whereas much effort has been targeted toward understanding the mechanism of IFN and potential IFN resistance, relatively little effort has been directed toward understanding RBV. RBV has been shown to play an important role in the treatment response (14), and higher RBV serum concentrations correlate with improved treatment outcome (26,34). However, we still do not understand how RBV works synergistically with IFN to improve SVR rates or whether resistance to RBV develops in patients.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Whereas much effort has been targeted toward understanding the mechanism of IFN and potential IFN resistance, relatively little effort has been directed toward understanding RBV. RBV has been shown to play an important role in the treatment response (14), and higher RBV serum concentrations correlate with improved treatment outcome (26,34). However, we still do not understand how RBV works synergistically with IFN to improve SVR rates or whether resistance to RBV develops in patients.…”
Section: Discussionmentioning
confidence: 94%
“…Perhaps elevated RBV uptake correlates with overall treatment success. Higher RBV serum concentrations have been associated with SVR (26,34). SVR rates of up to 90% have been achieved by using extremely high doses of RBV (35), albeit with increased toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the treatment of chronic HCV, ribavirin is currently dosed according to body weight, usually between 800 and 1,200 mg daily. 5 In a recent report by Hadziyannis et al, 3 patients with genotype 1 and a high viral load responded better to a ribavirin dose of 1,000 to 1,200 mg daily than to 800 mg/day combined with peginterferon. 3 In contrast to current recommendations, we have recently shown that renal function is of greater importance than body weight for ribavirin clearance, and we therefore have suggested the use of a pharmacokinetic formula based primarily on renal function as a tool to determine the accurate dose of ribavirin for treatment.…”
mentioning
confidence: 99%